2009
DOI: 10.1007/s00405-009-1084-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term anatomic and functional results of cartilage tympanoplasty in atelectatic ears

Abstract: The purpose of this study was to analyze the anatomic and functional results of cartilage tympanoplasty performed on atelectatic ears using the palisade technique and to assess the long-term efficacy of cartilage palisades in preventing recurrent retractions. The records of 54 patients (56 ears) who underwent surgery for atelectasis with or without mastoidectomy from January 2000 to August 2005 were retrospectively evaluated. A successful outcome was defined as complete and intact healing of the graft without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…In these studies, significant outcomes have been obtained in large series, with regard to at least 10 dB and a higher decrease in ABG. [3,4,6,7,18,20,37] The outcomes change according to the type of tympanoplasty; as was expected, better acoustic outcomes have been obtained in tympanoplasty type 1. [3,20] In ossicular reconstruction surgeries (TORP, PORP) or type 3 tympanoplasty, Austin obtained successful outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…In these studies, significant outcomes have been obtained in large series, with regard to at least 10 dB and a higher decrease in ABG. [3,4,6,7,18,20,37] The outcomes change according to the type of tympanoplasty; as was expected, better acoustic outcomes have been obtained in tympanoplasty type 1. [3,20] In ossicular reconstruction surgeries (TORP, PORP) or type 3 tympanoplasty, Austin obtained successful outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Ozbek et al 20 studied the long-term efficacy of cartilage palisades in TPL for atelectatic ears. The mean followup time was 44.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…The reported follow-up rates in the current literature are between 19.9 months and 12 years according to our search 3 7 20 - 22 . Mean follow-up time was 68.64 months in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Highrisk perforations including total, subtotal, atelectatic perforations, those with cholesteatoma and revision cases can be treated efficiently with cartilage reinforcement tympanoplasty [11] . It was also suggested that palisade cartilage tympanoplasty is an effective technique for tympanic membrane closure and hearing improvement in atelectatic ears, and mastoidectomy does not change the anatomic or audiologic findings in these types of ears [12] .…”
Section: Discussionmentioning
confidence: 99%